Effect of the temperature of cerium nitrate–NaCl solution on corrosion inhibition of mild steel. Issue 8 (30th January 2020) - Boudellioua, Hichem; Hamlaoui, Youcef; Tifouti, Lakhdar; Pedraza, Fernando
Abstract: In this study, the effect of temperature on corrosion inhibition is studied in the absence and presence of an optimal concentration of cerium nitrate (600 mg/L) as an inhibitor of mild steel in sodium chloride. Corrosion tests are carried out through electrochemical techniques such as impedance spectroscopy and d.c. polarization measurements. The surface morphology of the films is investigated by optical microscopy, white‐light interferometry, and scanning electronic microscopy, coupled with energy‐dispersive spectroscopy analysis for chemical composition. The results obtained show that the activation energy for the corrosion inhibition process to occur increases in the presence of a cerium nitrate inhibitor. However, the corrosion resistance of mild steel is somewhat lost upon increasing the solution temperature up to 55°C, which leads to more cracked films. The enthalpy and entropy values suggest a mixed mechanism of chemisorption and physisorption inhibition, with a major dominance of physisorption control. Abstract : The effect of temperature on corrosion inhibition is studied in the absence and presence of an optimal concentration of cerium nitrate as an inhibitor of mild steel in sodium chloride. The results show that the activation energy for the corrosion inhibition process to occur increases in the presence of cerium nitrate. However, the corrosion resistance is somewhat lost upon increasing the solution temperature up to 55°C